Marine Heat Waves and the Influence of El Niño off Southeast Queensland, Australia - Heidemann, Hanna; Ribbe, Joachim (Frontiers in Marine Science, 2019)
In this paper, we investigate the occurrence and spatial variability of marine heat waves (MHWs) off the southeast coast of Queensland, Australia. The focus is on identifying sea surface temperature (SST) variability in two key ecological hotspots located south of the Australian Great Barrier Reef. This coastal region is bordered in the east by the intensification zone of the East Australian Current (EAC). It includes Hervey Bay, which is part of a UNESCO declared marine biosphere and the Southeast Fraser Island Upwelling System. The analysis of remotely sensed SST for the period 1993 to 2016 identifies the largest number of MHW days for Hervey Bay with a mean length of 12 days. The maximum length of 64 days occurred during the austral summer 2005/2006. The years with the largest number of MHW days was found to occur following the El Niño events in 1998, 2010 and 2016. A cross-correlation and Empirical Orthogonal Function analysis identified a significant correlation with a time lag of seven months between SST anomalies in the Niño 3.4 region and the southeast Queensland coast. 78% of variance in SST anomalies is explained by the first mode of variability. The strength of the relationship with El Niño was spatially variable and the weakest in Hervey Bay. Due to its sheltered location and shallowness, it is argued that local weather patterns and air-sea fluxes influence this area more than the other two regions, where remotely forced changes in oceanic heat advection may have a stronger impact on generating MHWs. Biodiverse coastal shelf ecosystems are already under tremendous pressure due to human activities. This is likely to be compounded by continued climatic change and an increasing number of MHWs. Thus, similar studies are encouraged for other regional shelfs and smaller scale coastal systems.